2019
DOI: 10.1371/journal.pone.0225854
|View full text |Cite
|
Sign up to set email alerts
|

Drug overdose among women in intimate relationships: The role of partner violence, adversity and relationship dependencies

Abstract: BackgroundThis study examines the relationship between experiencing intimate partner violence (IPV), exposure to prior childhood adversity, lifetime adverse experiences, drug-related relationship dependencies with intimate partners and overdose, hospitalization for drug use, friends and family members who overdosed and witnessing overdose.MethodologyThis paper included a sample of 201 women who use drugs in heterosexual relationships with criminal justice-involved men in New York City. We included measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
(68 reference statements)
1
20
1
3
Order By: Relevance
“…This study found extremely high rates of severe physical and/or sexual IPV by both male and female partners that were significantly associated with experiencing an overdose and drug use hospitalizations. Although prior studies have found significant associations between IPV by a male partner or by any intimate partner and drug overdose (Ataiants et al, 2020;El-Bassel et al, 2019), to our knowledge this is the first study to find a significant association between IPV by a female partner and drug overdose indicators. The high rate of IPV by same sex partners indicates the need for a better understanding of how IPV may evolve and increase risks for overdose in same sex partnerships versus heterosexual partnerships.…”
Section: Np21516contrasting
confidence: 58%
See 1 more Smart Citation
“…This study found extremely high rates of severe physical and/or sexual IPV by both male and female partners that were significantly associated with experiencing an overdose and drug use hospitalizations. Although prior studies have found significant associations between IPV by a male partner or by any intimate partner and drug overdose (Ataiants et al, 2020;El-Bassel et al, 2019), to our knowledge this is the first study to find a significant association between IPV by a female partner and drug overdose indicators. The high rate of IPV by same sex partners indicates the need for a better understanding of how IPV may evolve and increase risks for overdose in same sex partnerships versus heterosexual partnerships.…”
Section: Np21516contrasting
confidence: 58%
“…Despite abundant research linking different experiences of violence to injection heroin use, the use of prescription opioids, benzodiazepines, and cocaine and other drugs responsible for overdose among women in general (Cafferky et al, 2018;El-Bassel et al, 2019;Gilbert et al, 2012Gilbert et al, , 2015Stone & Rothman, 2019) and Black women in particular (Nowotny & Graves, 2013), only a handful of studies have examined the relationship between experiencing different types of violence and drug overdose. The findings from these studies are mixed.…”
Section: Prior Research On the Relationship Between Different Types O...mentioning
confidence: 99%
“…For example, prevalence of intimate partner violence among people with OUD has been reported to be ∼50% (El-Bassel et al, 2005a). IPT and substance use commonly co-occur (Schneider et al, 2009;Williams et al, 2020) and may increase overdose risk (Ataiants et al, 2020;El-Bassel et al, 2019) as well as bring substantial physical and mental health risks (Bacchus et al, 2018;Phares et al, 2019), including homicide (VDH, 2018). Many people with OUD report lifetime IPT (Konkolÿ Thege et al, 2017), and importantly, IPT remains highly prevalent even after engaging with OUD treatment, in part due to inequities in social context (e.g., higher rates of poverty, unemployment, and homelessness) (de Dios et al, 2014;Velez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…62,63 Although the causal relationship between IPV and drug overdose among women in general has not been fully established, one study of abused women found an increased risk of overdose among those who had witnessed overdose, had lifetime drug use-related hospitalization, and had a relative or friend who experienced overdose. 64 The postpartum period may be a time of additional risk for pregnancy-associated overdose. Fatal and nonfatal overdose events decrease during the third trimester of pregnancy, with increased risk occurring at 7 to 12 months postpartum.…”
Section: Risk Factors Of Pregnancy-associated Death By Drug Overdosementioning
confidence: 99%
“… 62 , 63 Although the causal relationship between IPV and drug overdose among women in general has not been fully established, one study of abused women found an increased risk of overdose among those who had witnessed overdose, had lifetime drug use-related hospitalization, and had a relative or friend who experienced overdose. 64 …”
Section: Drug Overdose During Pregnancy and Pregnancy-associated Deatmentioning
confidence: 99%